THE ROLE OF SOUND DIRECTOR IN STAGE PRODUCTION: A COMPREHENSIVE ANALYSIS OF ARTISTIC AND TECHNICAL EXPERTISE (Academicia Globe: Inderscience Research, 2023)
In stage productions, the role of the sound director is critical to achieving a captivating and immersive experience for the audience. This scientific article explores the multifaceted responsibilities of a sound director, ranging from artistic creativity to technical proficiency. By examining the sound director's role, we aim to shed light on the importance of their contributions and the synergy they bring to a successful stage production.